تصميم بدن ناقلات النفط وحوادث التلوث النفطي - حوا رامي (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم لنا هذا البحث نتائج التحليل الشامل لحوادث ناقلات النفط من فئة معينة التي حدثت بين عامي (1978 و2003). هذه الدراسة تمكننا من إلقاء الضوء على معدلات وقوع الحوادث سنويا بالنسبة للحوادث الجسيمة. كما تكشف هذه الدراسة كذلك العلاقة بين تصميم بدن السفينة وخاصة (البدن المزدوج) والطرازات الأخرى من ناقلات النفط المصممة على أساس وجود بدن واحد, والحوادث التي تتعرض لها هذه الناقلات, بالإضافة إلى تحرّي العلاقة بين عمر السفينة ومعدلات وقوع الحوادث البحرية بقصد معرفة أعداد الناقلات ذات البدن الواحد وتلك المصممة على أساس بدنين من مختلف فئات الأعمار. سنقوم بهذا البحث بالاستقصاء عن وجود علاقة محتملة بين تصميم بدن ناقلات النفط (ناقلات نفط ذات بدن واحد وأخرى ذات بدن مزدوج) وحوادث التلوث النفطي. وسيتم حساب معدلات وقوع الحوادث على أساس نوع الحادثة ونمط تصميم بدن الناقلة. The paper presents results of a comprehensive analysis of recorded accidents of a special category of tankers, which occurred in the period between 1978 and 2003. The analysis identifies the significant trends with respect to accident rates per shipyard for all major accident categories. It also investigates the relationship between the age of tankers and ship accidents ratio. It also relates the impact of hull design of the ship, namely of the double hull and the various non-double hull configurations, as well as the impact of the age of the ship to tanker accidents. Moreover, the paper investigates the possible relationships between the hull design of the tanker (Double Hull and various Non-Double hull configurations) and oil pollution. Calculations of accident rates were conducted by category of accidents and the type of the hull design of ship.